2018
DOI: 10.1016/s0140-6736(18)31813-0
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic efficacy and safety of morphine in the Procedural Pain in Premature Infants (Poppi) study: randomised placebo-controlled trial

Abstract: SummaryBackgroundInfant pain has immediate and long-term effects but is undertreated because of a paucity of evidence-based analgesics. Although morphine is often used to sedate ventilated infants, its analgesic efficacy is unclear. We aimed to establish whether oral morphine could provide effective and safe analgesia in non-ventilated premature infants for acute procedural pain.MethodsIn this single-centre masked trial, 31 infants at the John Radcliffe Hospital, Oxford, UK, were randomly allocated using a web… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 30 publications
0
100
0
Order By: Relevance
“…While this time window may not be appropriate for longer procedures, and consideration of other non‐noxious control stimuli is needed, using a data‐driven approach such as the one used here may identify features within physiological responses which are accurate surrogate measures of infant pain. Moreover, in the case of clinical trials of analgesics, including multiple modalities is beneficial in the assessment of safety, as well as efficacy, of a drug …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While this time window may not be appropriate for longer procedures, and consideration of other non‐noxious control stimuli is needed, using a data‐driven approach such as the one used here may identify features within physiological responses which are accurate surrogate measures of infant pain. Moreover, in the case of clinical trials of analgesics, including multiple modalities is beneficial in the assessment of safety, as well as efficacy, of a drug …”
Section: Discussionmentioning
confidence: 99%
“…While this time window may not be appropriate for longer procedures, and consideration of other non-noxious control stimuli is needed, using a data-driven approach such as the one used here may identify features within physiological responses which are accurate surrogate measures of infant pain. Moreover, in the case of clinical trials of analgesics, including multiple modalities is beneficial in the assessment of safety, as well as efficacy, of a drug 41,42. Here, we considered responses to a clinically required heel lance and compared them to responses to a non-noxious control stimulus.These stimuli were closely matched, allowing us to identify features that could discriminate the noxious component of the procedure.…”
mentioning
confidence: 99%
“…However, as mentioned earlier, in the POPPI study, oral morphine (100 µg/kg) was associated with either a higher incidence of newly occurring apneic events or an increase in the number of such events in the morphineexposed group. Because of these safety-related findings (sufficient evidence of harm), the POPPI study was terminated early (10). Based on the currently available evidence, it seems that a non-pharmacological intervention, based on a bundled developmental care intervention concept, resulted in a clinically relevant reduction in the pain and stress responses and in the time needed to recover (69).…”
Section: Paracetamol For Acute Procedural Analgesia In Neonatesmentioning
confidence: 99%
“…The reported short-term side effects associated to opioid exposure in preterm neonates include hypoventilation and apnea, low blood pressure, intestinal hypoperistalsis, and bladder dysfunction. Hypoventilation and apnea resulted in prolonged duration [7 (4-20) days in morphine-exposed group compared to 6 (3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19) days in the placebo group, + 1 day of ventilation] (9). Along the same line, Hartley et al recently reported that morphine (single oral, 100 µg/kg dose) in non-ventilated preterm infants, used to facilitate the screening for retinopathy of prematurity (ROP) in the Procedural Pain in Premature Infants (POPPI study) and to blunt the pain response, resulted in a high incidence (8/15 vs. 3/15, relative risk 2.7, number needed to harm = 3) of either newly occurring apneic events or an increase in the number of such events in the morphine-exposed group (10).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation